Pendidikan Kesehatan Berkelanjutan tentang Diabetes pada Media Sosial Online - Nila Kusumawati; Abdul Hamid; Achmad Jajuli (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Health education about diabetes plays an important role in preventing and controlling diabetes. The aim of this community service activity is to provide ongoing health education about diabetes using online social media. This activity will start from February to November 2023 and includes creating social media accounts, publishing diabetes-related material on social media, socializing the existence of social media to the public, and monitoring and evaluating health education that has been carried out. This activity resulted in four social media accounts about diabetes with a total of 221 posters, 78 videos, 585 followers/subscribers, 10.906 viewers, and 948 likes. Access to health education about diabetes is mostly accessed by people of the female gender and in the age range of 25-34 years. Continuous health education is needed to increase public awareness about diabetes because it does not require a lot of time, energy, and costs and can reach a wider community. The quality of media and health education materials needs to be considered to continue to increase public interest in increasing their knowledge about diabetes.